Community forest Dependency: Does Distance Matter? - Ghosal, Somnath; Liu, Jinlong (Indian Forester, 2017)
With the recent economic and cultural trends, combined with the appeal of the tropical forests management and its indigenous communities livelihoods have led to the growing implementation of partnerships for sustainable forest products trade. The role of stakeholders including villagers, forest products sellers, NGOs and other associates need to be re-examined from the aspect of forest dependency. Sustainable forest products consumption or marketing by the forest dwellers may improve their livelihoods and subsequently improve the forest quality. Distance between forest and the nearest villages is an important factor for examine the level of dependency on forest harvesting. However, with the local market proximity the purpose of collection changed significantly. The present study will examine how the distance between forest, villages and local market determine the forest dependency pattern in case of Indian forestry.